2017
DOI: 10.21577/0103-5053.20170147
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Composition of Corrosion Product Film and its Relation to Corrosion Rate for Carbon Steels in CO2 Saturated Solutions at Different Temperatures

Abstract: For carbon steels immersed in CO 2 saturated solutions at different temperatures, the structure and the composition of corrosion product film formed on the steel surface were studied by scanning electron microscope (SEM), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). The corrosion rate of the steel was evaluated by potentiodynamic polarization, and the relation between the corrosion rate and the film property was discussed. The corrosion rate of the steel was very closely associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…17 However, for the surface passivation of carbon steels in acidic environments, the effectiveness of NO 2 is very few reported, and the detailed mechanism of NO 2 is still not completely clear. Zhou et al [19][20][21] systemically investigated the influences of NaNO 2 addition and its concentration on the corrosion and passivation of Q235 carbon steel in CO 2 saturated solution (pH 3.7). The electrochemical behavior of Q235 carbon steel transferred from the activation in CO 2 saturated solution free of NaNO 2 to the passivation in the same solution containing NaNO 2 ; 19 with the increase of NaNO 2 concentration, the passivation capability of Q235 carbon steel was strengthened obviously until the NaNO 2 concentration was up to 0.05 mol L -1 ; 20 the mechanism of NO 2 on the surface passivation was very closely associated with the formation of Fe 2 O 3 passive film under FeCO 3 corrosion product layer.…”
Section: Nomentioning
confidence: 99%
See 1 more Smart Citation
“…17 However, for the surface passivation of carbon steels in acidic environments, the effectiveness of NO 2 is very few reported, and the detailed mechanism of NO 2 is still not completely clear. Zhou et al [19][20][21] systemically investigated the influences of NaNO 2 addition and its concentration on the corrosion and passivation of Q235 carbon steel in CO 2 saturated solution (pH 3.7). The electrochemical behavior of Q235 carbon steel transferred from the activation in CO 2 saturated solution free of NaNO 2 to the passivation in the same solution containing NaNO 2 ; 19 with the increase of NaNO 2 concentration, the passivation capability of Q235 carbon steel was strengthened obviously until the NaNO 2 concentration was up to 0.05 mol L -1 ; 20 the mechanism of NO 2 on the surface passivation was very closely associated with the formation of Fe 2 O 3 passive film under FeCO 3 corrosion product layer.…”
Section: Nomentioning
confidence: 99%
“…Zhou et al [19][20][21] systemically investigated the influences of NaNO 2 addition and its concentration on the corrosion and passivation of Q235 carbon steel in CO 2 saturated solution (pH 3.7). The electrochemical behavior of Q235 carbon steel transferred from the activation in CO 2 saturated solution free of NaNO 2 to the passivation in the same solution containing NaNO 2 ; 19 with the increase of NaNO 2 concentration, the passivation capability of Q235 carbon steel was strengthened obviously until the NaNO 2 concentration was up to 0.05 mol L -1 ; 20 the mechanism of NO 2 on the surface passivation was very closely associated with the formation of Fe 2 O 3 passive film under FeCO 3 corrosion product layer. 21 Further, Zhou et al 22 also investigated the influence of NaNO 2 addition on the electrochemical behavior of Q235 carbon steel in pH 1 to 6 HCl solutions.…”
Section: Nomentioning
confidence: 99%
“…8,11,13 However, in acidic media, the related studies involving NO 2 − are relatively few, and the present studies are summarized as follows. In carbon dioxide (CO 2 ) corrosion environments, Zhou et al [15][16][17][18] studied the influence of NO 2 − on the corrosion / passivation behavior of Q235 carbon steel in CO 2 saturated solution (pH 3.7) in detail.The Q235 steel presented the electrochemical behavior of activation in CO 2 saturated solution without NO 2 − ; 15 after the addition of NO 2 − , the electrochemical behavior transferred from activation to anodic passivation, and the critical NO 2 − concentration for the stable passivation was approximately 0.05 mol L -1 ; 16 intergranular corrosion (IGC) was observed on the surface of Q235 carbon steel when the Q235 steel was polarized into activation-passivation potential region with a low potential scanning rate; 17 the occurrence of IGC was very closely associated with the electrochemical behavior of activation-passivation transition, which was resulted from the synergetic mechanisms of CO 2 and ΝΟ 2 − . 18 In other 19 studied the combined influences of NO 2 − and thioureido imidazoline (TAI) on the passivation behavior and the pitting corrosion (PC) of X70 carbon steels in acidic NaCl solution (pH 5.5) and reported that the mechanisms of NO 2 − and TAI were both interactive and superimposed, and the addition of NO 2 − was beneficial to restrain the initiation and propagation of PC.…”
Section: Introductionmentioning
confidence: 99%
“…Practically, few recent studies discussing the common and localized corrosion of copper alloys in seawater have been reported. 7,8 Recently, the use of corrosion inhibitors has become one of the most important ways to reduce corrosion attacks, which prevent copper dissolution in an aggressive medium by forming adsorbed barrier layer at the metal surface and by decreasing the metal/solution contact. 9,10 Different types of inhibitors used should be safe besides being eco-friendly and economical.…”
Section: Introductionmentioning
confidence: 99%